Field test of uplink CoMP joint processing with C-RAN testbed - Lei Li; Jinhua Liu; Kaihang Xiong; Butovitsch, Peter (2012 7th International ICST Conference on Communications and Networking in China, 2012)
Uplink Coordinated Multi-Point (CoMP) joint processing has the potential to improve uplink capacity by joint processing the received signal from more antennas and nodes. With C-RAN architecture, centralized and coordinated baseband processing among base stations become feasible. This paper introduces LTE uplink CoMP joint processing - the principles, simulation evaluations, field testbed and test results. The field test is done with C-RAN field testbed which is built around Ericsson office in Beijing. Both the simulation evaluations and field test results show that uplink CoMP has great gain at the cell edge especially when there is interference, so it can be a good solution to improve the cell edge throughput of the LTE system.